DD-023 Evaluation of information content and characteristics of publicly available drug shortage information sources. (14th February 2016) - Vida, RG; Fittler, A; Botz, L
Abstract : Background: As drug shortages continue to pose an international problem almost every country has implemented a shortage information source in the form of a catalogue or database system. The aim of these systems is to collect and provide information about supply disruptions and therefore help mitigate the effect on the healthcare system and patient care. Unfortunately, these databases are heterogeneous which raise difficulties for hospital pharmacists. Purpose: Our aim was to assess the information content and characteristics of publicly available shortage databases to identify and draw attention to the problem. The signalling function (collection mechanism, source of data and frequency of update) was also evaluated as a key parameter in everyday practice. Material and methods: 6 European and 4 oversea s (South America and Australia) online available drug shortage information sources (catalogue, database) were evaluated according to the following characteristics: (1) product information: product name, name of active ingredient, dosage form, unit size, identification number/marketing authorisation number, marketing authorisation holder, ATC code or therapeutic category; (2) shortage information: duration–beginning and estimated end, reason/background, recommendations; and (3) database structure: language, status, variety of pharmaceuticals included, owner, references, updates, searching options. Results: Every database (100%) contained data about the product, active ingredient, dosage form, notification or beginning of the shortage event and the reason or background of the supply disruption. Special features were observed in some databases, such as the representation of information source (40%), alternative product recommendation (20%), patient safety precautions (10%) and information for patients (10%). All of the databases contained information about the notification system but it was represented as separate information. Conclusion: The national drug shortage databases show a high degree of diversity in information content and structure. A standardised reporting system is advisable at international, national and institutional levels. The required and presented information may vary regarding the location and level of health service provision, but inclusion of product identification information, duration (beginning and estimated end) and comprehensive signalling function is highly recommended for the efficient management of supply disruptions. No conflict of interest.